Efeitos do uso agudo do donepezil sobre habilidade visuoespaciais de voluntários jovens sadios - Zaninotto, Ana Luiza Costa [UNIFESP] (2009)
Rationale: Drugs such as donepezil that increase the availability of acetylcholine (Ach) are known to improve cognition. However, there is no consensus as to the acute nootropic potential of this drug when administered to young, healthy volunteers. In the studies that have investigated this issue donepezil effects were evaluated before peak-plasma concentration was reached. Hence, lack of consistent results may reflect performance at suboptimal and/or variable concentrations of ACh. Objective: To evaluate the time course of cognitive effects of an acute oral dose of donepezil in young, healthy volunteers. Methods: This was a double-blind, placebo controlled, parallel group study of cognitive effects of acute oral donepezil (5 mg). Subjects were tested twice after donepezil ingestion: 90 min (time that coincides with previous testing in the literature) and 210 min. (theoretical peak-plasma concentration). The test battery included tasks that tap cognitive domains that have been shown to be sensitive to ACh manipulations: visuospatial processing, episodic memory, and subcomponents of working memory, in addition to evaluations of mood. Results: Most of donepezil’s effects were observed at both testing times and included improvement in mood, long-term recall of prose, objects recall, recall of static spatial locations and integration of objects with their locations. However, improvement of performance in the central executive measure (backward digit span) occurred only at 210 min. Conclusion: positive cognitive effects of acute donepezil can be observed in various cognitive domains in young, healthy volunteers but its full nootropic potential is more clearly found close to peak-plasma concentration.